Phenotype and Genotype Characterisation of the Asian Clam of the Genus Corbicula Megerle von Mϋhlfeld, 1811 (Venerida, Cyrenidae) from the East Coast of Peninsular Malaysia - Ramli, Mohd Zharif; Ayyapan, Vinothiran; Yusoff, Akrimah; Eh Rak, Aweng; Lee, Seong Wei (Borneo Journal of Resource Science and Technology, 2020)
The Corbicula taxonomy in Malaysia is equivocal and scarcely being reported. This study aims to characterise phenotype and genotype of the Asian clam of the genus Corbicula (Mergele Von Mühlfeld, 1811) from three locations in east coast of Peninsular Malaysia. The phenotypic characterisation of the three population of the clam was evaluated on the basis of morphometric characters, while mtDNA cytochrome b (cytb) was used to characterise the genotypes. Results of morphometric analysis showed a significant difference (p<0.05) in shell height (SH), shell width (SW) and umbo length (UL) among three locations between the evaluated population. Discriminant analysis also revealed significant difference of the characters among the study sites. However, cluster analysis revealed an overlapping of morphometric characters among evaluated C. fluminea intricate complete separation between populations. Besides, a comparison of the Corbicula with the morphotypes and holotypes had proposed the Corbicula in this region known as C. fluminea. The genotypes characterisation using mtDNA cytb verifies the existence of C. fluminea. Phylogenetic trees demonstrated polymorphism and low genetic variances although geographically separated which parallel to the phenotypic characterisation. Thus, these findings enhance the knowledge on geographical variation and elucidate the complexity of taxa.